Pengaruh Litersi Keuangan dan Teman Sebaya terhadap Perilaku Konsumtif Mahasiswa: Studi Kasus pada Mahasiswa FKIP Universitas Nusa Cendana - Jeni Soli Naga (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study aims to analyze the influence of financial literacy and peers on the consumptive behavior of FKIP students of Nusa Cendana University, both partially and simultaneously. The phenomenon of increasing lifestyle-based consumption, trends, and social recognition indicates a shift from need-to-desire orientation, which has the potential to weaken student financial stability. This research is expected to make a theoretical contribution to the development of student financial behavior studies and become the basis for practical considerations for institutions in designing programs to strengthen financial literacy. The study uses a quantitative approach with a causal associative design. The population amounted to 8,775 students, with a sample of 165 respondents determined through incidental sampling techniques. Data is collected through questionnaires that have been tested for validity and reliability. Data analysis was carried out using multiple linear regression after meeting classical assumption tests, including normality, linearity, multicollinearity, and heteroscedasticity. The results of the study show that financial literacy has a positive and significant effect on consumptive behavior, meaning that increasing financial literacy significantly increases students' tendency to over-consume. Peers have a positive and significant influence which means that the stronger the influence of the friendship environment, the higher the consumptive behavior. Simultaneously, the two variables have a significant effect on the consumptive behavior of students. These findings affirm the importance of increasing financial literacy capacity and fostering a constructive social environment to suppress students' consumptive tendencies.